Efficacy of Indoor Residual Spraying Using Lambda-Cyhalothrin for Controlling Nontarget Vector Fleas (Siphonaptera) on Commensal Rats in a Plague Endemic Region of Northwestern Uganda - Borchert, Jeff N.; Eisen, Rebecca J.; Atiku, Linda A.; Delorey, Mark J.; Mpanga, Joseph T.; Babi, Nackson; Gage, Kenneth L.; Enscore, Russell E. (Journal of medical entomology, 2014)
Over the past two decades, the majority ofhumanplague cases have been reported from areas in Africa, including Uganda. In an effort to develop affordable plague control methods within an integrated vector control framework, we evaluated the efÞcacy of indoor residual spraying (IRS) techniques commonly used for mosquito control for controlling ßeas on hut-dwelling commensal rodents in a plague-endemic region of Uganda. We evaluated both the standard IRS spraying (walls and ceiling) and a modiÞed IRS technique that included insecticide application on not only on walls and ceiling but also a portion of the ßoor of each treated hut. Our study demonstrated that both the standard and modiÞed IRS applications were effective at signiÞcantly reducing the ßea burden and ßea infestation of commensal rodents for up to 100 d after application, suggesting that IRS could potentially provide simultaneous control of mosquito and ßeaborne diseases.
Keywords: Indoor residual spray; Rattus rattus; Plague; ßea; Lambda-cyhalothrin